The Role of Return on Assets in Moderating the Effect of Economic Value Added and Market Value Added on Banking Share Prices on the IDX for the 2019-2023 period - Supriyanto, Supriyanto; Leonardo, Angga Francesco; Rabeta, Yulpa (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2025)
The purpose of this study is to examine how market value added (MVA) and economic value added (EVA) affect the share prices of banking subsector companies that are listed on the Indonesia Stock Exchange (BEI) between 2019 and 2023. The moderating effect of Return on Assets (ROA), which is believed to affect the relationship between Market Value Added and Economic Value Added on stock prices, is also tested in this study. Quantitative research methodology is employed. Panel data from 23 banking companies that met the sample criteria during the research period makes up the research data. Panel data regression using the Fixed Effect Model (FEM) and interaction testing to assess the moderating effect are the analytical techniques employed. According to the study's findings, economic value added has little bearing on stock prices and is not statistically significant, suggesting that investors may give it less consideration. Conversely, market value added has a big impact on share prices, which shows that investors value the value that is added for shareholders. Stock prices are significantly impacted by both Market Value Added and Economic Value Added at the same time. Return on Assets can, nonetheless, limit the impact of Market Value Added, where the degree of Return on Assets determines how strongly Market Value Added influences share prices. It cannot, however, moderate the impact of Economic Value Added on stock prices.